TSPTFBS 2.0: trans-species prediction of transcription factor binding sites and identification of their core motifs in plants - Cheng, Huiling; Liu, Lifen; Zhou, Yuying; Deng, Kaixuan; Ge, Yuanxin; Hu, Xuehai (Frontiers in Plant Science, 2023)
An emerging approach using promoter tiling deletion via genome editing is beginning to become popular in plants. Identifying the precise positions of core motifs within plant gene promoter is of great demand but they are still largely unknown. We previously developed TSPTFBS of 265 Arabidopsis transcription factor binding sites (TFBSs) prediction models, which now cannot meet the above demand of identifying the core motif. Here, we additionally introduced 104 maize and 20 rice TFBS datasets and utilized DenseNet for model construction on a large-scale dataset of a total of 389 plant TFs. DenseNet not only has achieved greater predictability than baseline methods such as LS-GKM and MEME for above 389 TFs from Arabidopsis, maize and rice, but also has greater performance on trans-species prediction of a total of 15 TFs from other six plant species. More importantly, we combined three biological interpretability methods including DeepLIFT, in-silico tiling deletion, and in-silico mutagenesis to identify the potential core motifs of any given genomic region. A motif analysis based on TF-MoDISco and global importance analysis (GIA) further provide the biological implication of the identified core motif. Finally, we developed a pipeline of TSPTF BP 2.0, which integrates 389 DenseNet-based models of TF binding and the above three interpretability methods. This pipeline was implemented as a user-friendly web-server (http://www.hzau-hulab.com/TSPTFBS/), which can support important references for editing targets of any given plant promoters and it has great potentials to provide reliable editing target of genetic screen experiments in plants.